Investigation of very high cycle fatigue by thermographyc method - V. Crupi; G. Epasto; E. Guglielmino; G. Risitano (Fracture and Structural Integrity)
Nowadays, many components and structures are subjected to fatigue loading with a number of cycles higher than 107. In this scientific work, the behaviour of two kinds of tool steel was investigated in very high cycle fatigue regime. The fatigue tests were carried out at the frequency of 20 kHz and in fully reversed tensioncompression mode (R = -1) by means of an ultrasonic fatigue testing equipment. The radiometric surface temperature was detected during all the test by means of an IR camera in order to extend the Thermographic Method and the Energetic Approach in very high cycle fatigue regime. The failure mechanism of the investigated steels was evaluated by means of several experimental techniques (scanning electron microscopy, Energy Dispersive X-ray spectroscopy and Optical Microscopy).